Fotografi Musik dalam Perkembangan Musik Band Burgerkill - Mohammad Yusrirrizqi; Wiki Angga Wiksana (Bandung Conference Series: Communication Management, 2024)
Abstract. Music photography is a branch of photography that is quite popular with many people. Photos that focus on capturing moments in the world of music. Along with the development of the music industry and the high popularity of music, music photography has become an important element in documentation and promotion. The development of music photography seems to always be side by side with the development of music. Especially in the development of music in the city of Bandung. This research aims to determine music photography in the development of the Burgerkill band's music. In this research, researchers used qualitative methods with a case study approach. Then the paradigm used is the constructivism paradigm. Researchers sought in-depth information through interviews addressed to the Burgerkill band photographer, one of the Burgerkill band members, and fans of the Burgerkill band's music. Photography is one part of the axis of development of the band Burgerkill's music, but basically it is not music that changes the music ecosystem, because if we talk about the ecosystem too broadly, perhaps the most appropriate thing is that music encourages photography in creating its own ecosystem, creating classes of expertise specifically in the realm of photography. Abstrak. Fotografi musik menjadi salah satu cabang fotografi yang cukup diminati oleh banyak orang. Foto yang berfokus dalam pengabadian momen di dunia permusikan. Seiring dengan perkembangan industri musik dan popularitas musik yang tinggi, fotografi musik telah menjadi suatu elemen penting dalam perdokumentasian hingga promosi. Perkembangan fotografi musik sepertinya akan selalu berdampingan dengan perkembangan musik. Terkhusus dalam perkembangan musik di kota Bandung. Penelitian ini bertujuan untuk mengetahui fotografi musik dalam perkembangan musik band Burgerkill. Dalam penelitian ini peneliti menggunakan metode kualitiaf dengan pendekatan studi kasus. Lalu paradigma yang dipakai adalah paradigma konstruksivisme. Peneliti mencari informasi yang mendalam melalu wawancara yang ditujukan kepada fotografer band Burgerkill, salah satu personil band Burgerkill, dan penikmat musik-musik band Burgerkill. Fotografi menjadi salah satu bagian dalam poros perkembangan musik band Burgerkill, namun pada dasarnya bukan musik yang merubah ekosistem musik, karena jika berbicara tentang ekosistem itu terlalu luas, mungkin yang paling tepat adalah musik mendorong fotografi dalam menciptakan sebuah ekosistemnya sendiri, menciptakan kelas-kelas keahlian tertentu di ranah fotografi.